Submucosal Giant Lipoma of the Colon as an Unusual Cause of Partial Intestinal Occlusion: Report on Seven Consecutive Cases - Kafadar, Mehmet Tolga; Dalbaşı, Erkan; Oğuz, Abdullah; Aday, Ulaş (Turkish Journal of Gastroenterology, 2021)
Background: Colonic lipomas begin to be symptomatic when they reach a certain size, although the presentation can vary. In this study,we aimed to evaluate our experiences with the management of patients who presented with symptomatic giant colonic lipomas.Methods: The data of 7 patients with single colonic lipoma were retrospectively reviewed. The following data were evaluated: age, gender,clinical and diagnostic findings, American Society of Anesthesiologists (ASA) score, operative findings, postoperative complications,mortality, hospital stay duration, and hospital readmission. The diagnosis of colonic lipoma was established by computed tomography(CT).Results: In this study, 4 (57.1%) of 7 patients with colonic lipoma were female, and 3 (42.9%) were male. The mean age was 56.7 years(range, 45-69). The main symptoms were abdominal pain (100%), and constipation (71.4%). The findings of intestinal occlusion detectedon CT confirmed the diagnosis in all patients. Colon lipoma was located in the ascending colon in 2 patients, in the hepatic flexure in2 patients, in the transverse colon in 2 patients, and in the cecum in 1 patient. The surgical procedure was uneventful in all patients. Four(57.1%) patients underwent laparoscopic colonic resection, while in the remaining 3 (42.9%) patients, a laparotomy was performed. Themean operating time was 185.7 min (150-210). Length of stay was 7.1 days (6-10), with no mortality. The mean diameter of the lesionswas 7.4 cm (6-9). At a 6-month follow-up, all patients were asymptomatic with no signs of recurrence.Conclusion: Although colon lipomas are rare, they are of great importance because they can be symptomatic and can be confused withcolon malignancies in the differential diagnosis. Being able to make a definitive preoperative diagnosis will change the surgical strategy.A minimally invasive surgical approach should be employed to resect symptomatic colonic lipomas with an experienced surgical teamin eligible patients whenever possible.